The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s00521-010-0495-0
|View full text |Cite
|
Sign up to set email alerts
|

Credit rating modelling by kernel-based approaches with supervised and semi-supervised learning

Abstract: This paper presents the modelling possibilities of kernel-based approaches to a complex real-world problem, i.e. corporate and municipal credit rating classification. Based on a model design that includes data pre-processing, the labelling of individual parameter vectors using expert knowledge, the design of various support vector machines with supervised learning as well as kernel-based approaches with semi-supervised learning, this modelling is undertaken in order to classify objects into rating classes. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…It was shown that support vector machines significantly outperform logistic regression models, particularly under the condition of small training samples and high variance of the input data. Further, in 2010 Peter Hajek and Vladimır Olej [16] have presented the modeling possibilities of kernel-based approaches to a complex real-world problem, i.e. corporate and municipal credit rating classification.…”
Section: Related Workmentioning
confidence: 99%
“…It was shown that support vector machines significantly outperform logistic regression models, particularly under the condition of small training samples and high variance of the input data. Further, in 2010 Peter Hajek and Vladimır Olej [16] have presented the modeling possibilities of kernel-based approaches to a complex real-world problem, i.e. corporate and municipal credit rating classification.…”
Section: Related Workmentioning
confidence: 99%
“…This paper tried to compare backpropagation neural network as a benchmark with the new technique. Later, Cao et.al [15], Lee [16]and Hajek and Olej [17] compared SVM with the backprogation (BP) neural network, and traditional statistical methods such as; logistic regression (LR) and ordered probit regression (OPR) with Support Vector Machine (SVM).…”
Section: B Previous Studies On Bond Rating Predictionsmentioning
confidence: 99%
“…These sources of finance influence the credit rating process of these entities. Municipal credit rating is based on the analysis of four categories of variables, namely economic, debt, financial, and administrative (Hajek and Olej 2011). Economic variables include socio-economic conditions such as population, unemployment, and local economy concentration.…”
Section: Variable Selection In Datasetsmentioning
confidence: 99%
“…The difficulty in designing such models lies in the fact that there are complex relations between financial and other variables. Recently, soft-computing methods such as neural networks (NNs) (Brennan and Brabazon 2004;Hajek 2010Hajek , 2011, support vector machines (Huang et al 2004;Lee 2007), artificial immune systems (Delahunty and O'Callaghan 2004), evolutionary algorithms (Brabazon and O'Neill 2006), case based reasoning (Lee 2007), and semi-supervised methods (Hajek and Olej 2011) have been used for both municipal and corporate credit rating analysis.…”
Section: Introductionmentioning
confidence: 99%